The Implementation of Integrated Character Education in Policy Design at SD Muhammadiyah (Plus) Salatiga - Azhary, Luqman; Handoyo, Eko; Khafid, Muhammad (Journal of Primary Education, 2018)
This study aims to describe the implementation of character education in SD Muhammadiyah (Plus) Salatiga. This research applied descriptive method with qualitative approach. The data analysis was collected through semi-structured interviews, observation and documentation study. The data validity technique was done by using triangulation technique and resources.The results of this study showed that SD Muhammadiyah (Plus) Salatiga has run character education which is integrated in the school's policy, it is evidenced by the inclusion of character values environmental care, religious, autonom, love of the homeland, polite and courteous into the vision, mission and school programs. The characters of honest, thorough, innovative and independent also have been integrated in the classroom, it is seen in the Lesson Plan and the media that were created by teachers.The school also has instilled a religious character, cooperation and empathy in the community-based character education, it is evidenced by their happy Ta'jil event in Ramadan, the distribution of basic food parcels for poor people around the school and pray Eid or Eid al-Adha together, The event was held as gratitude to the cooperation between the school, the bond of students’ guardian, school committees and the school has a strategies plan to outcome by carakter buildings. The problems encountered in this study include the lack of facilities for the implementation of character education, strengthen the character education in the future.